Sustainable Development Goals: Their Impacts on Forests and People 2019
DOI: 10.1017/9781108765015.012
|View full text |Cite
|
Sign up to set email alerts
|

SDG 10: Reduced Inequalities – An Environmental Justice Perspective on Implications for Forests and People

Abstract: SDG10 has the potential to reflect a core commitment within the SDGs-'leave no one behind'-and to recognise that the dominant economic system exacerbates inequalities within countries through rules that reinforce the current global distribution of wealth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 136 publications
0
9
0
Order By: Relevance
“…Synthesis work was anchored in ongoing processes of global importance. For example, as the Sustainable Development Goals (SDGs) were identified, FTA produced several works linking gender, inequality and natural resource management and forest outcomes to this global agenda Arora-Jonsson et al 2019;Sijapati Basnett et al 2019). FTA further contributed to assessments of the implementation of global agendas, including IUFRO's Global Assessment on Forests and Poverty (Hajjar et al 2020) and the Assessment of the New York Declaration of Forests' Goal 10, which addresses the persistence of gender bias in forest governance (Conway et al 2018, NYDF 2018.…”
Section: Photo By Yoly Gutierrez/ciformentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis work was anchored in ongoing processes of global importance. For example, as the Sustainable Development Goals (SDGs) were identified, FTA produced several works linking gender, inequality and natural resource management and forest outcomes to this global agenda Arora-Jonsson et al 2019;Sijapati Basnett et al 2019). FTA further contributed to assessments of the implementation of global agendas, including IUFRO's Global Assessment on Forests and Poverty (Hajjar et al 2020) and the Assessment of the New York Declaration of Forests' Goal 10, which addresses the persistence of gender bias in forest governance (Conway et al 2018, NYDF 2018.…”
Section: Photo By Yoly Gutierrez/ciformentioning
confidence: 99%
“…The engagement of FTA gender researchers in high-level processes related to the Convention on Biological Diversity's (CBD) post-2020 Global Biodiversity Framework, the UN Decade on Ecosystem Restoration, and the Global Environment Facility's expert group on gender has demonstrated an increasing emphasis on achieving synergies among a range of environmental targets and among environmental and gender equality goals. This has led to FTA gender-focused work exploring synergies and trade-offs among such goals, as well as strategies and approaches that support the achievement of mutual benefits (Djoudi et al 2013;Arora-Jonsson et al 2019;Sijapati Basnett et al 2019;Elias et al 2020b). This work has generated considerable interest among multilateral conventions and organizations, exemplified by an ongoing collaboration with UN Women for a paper on achieving synergies across the Rio Conventions from a gender perspective.…”
Section: Moving Forwardmentioning
confidence: 99%
“…Moreover, implementation of zero deforestation commitments is incredibly complex due to supply chain growth to continue as usual (Cavanagh and Benjaminsen 2014). Private certification has been promoted as an important private forest governance solution, but can reinforce new forms of injustices as it privileges those who can afford to dedicate time and resources to comply with complicated standards (Basnett et al 2019). According to Sayer et al (2019, p. 501): "Without an emphasis on integration, wide political and public engagement and greater responsiveness to local needs, SDG 15 risks perpetuating a sectoral, top-down approach".…”
Section: Governance Across Scales: Translations and Enactments Of Sustainable Forest Governancementioning
confidence: 99%
“…Current global sustainable forest governance initiatives are underpinned by the notion of forests as a 'global common good', which may contrast with local understandings of forests and in turn create barriers to transitioning to zero deforestation (Basnett et al 2019). 'Global' views of legality, such as those defined by the EU Forest Law Enforcement, Governance and Trade (FLEGT) Action Plan, for example, differ from local understandings of legality which are viewed by non-state actors as part of a colonial legacy and imposed upon them (Myers et al 2020).…”
Section: Can Justice Respect Needs and Nature?mentioning
confidence: 99%
“…(Continued).Supranational policies addressing illegal logging by cutting off markets for illegally harvested timber, and private certification of sustainable forest products, serve as forms of forest governance that bypass the state and may reinforce or create new forms of distributive injustice(Basnett et al 2020) Considerable synergies and complementarities can be found between the SDG 10 targets and the goals of environmental justice, which comprise three interrelated dimensions: representational, recognition and distributive justice However, the disjuncture between SDG 10 and environmental goals within the SDGs may undermine efforts to promote environmental justice…”
mentioning
confidence: 99%